Diversity of frogs in Tawau Hills Park, Sabah, Malaysia - Yong Huaimei; Anna Wong; Muhammad Afif Zakaria (Universiti Malaysia Sabah, 2019)
A study on the diversity of anurans was carried out via Visual Encounter Survey (VES) method in Tawau Hills Park (THP), from June 2009 to September 2010. Twenty-eight line transects were established and surveyed, resulting in 925 individuals from 51 species, representing six families. Eighteen species were new locality records for THP, bringing the total number of identified frogs to 68 species. These frogs occupy elevations from lowland area (200 m a.s.l.) at the headquarters of THP, Balong substation and Merotai substation to submontane area (>900 m a.s.l.) at Mount Maria, Mount Lucia and Mount Magdalena. All 68 species recorded represent 62% of the total frog species found in Sabah, with 15% of them endemic to Borneo. Frog species in THP were dominated by Ranidae (39.4%) and Dicroglossidae (24.4%). Limnonectes leporinus was the most abundant species (10.2%), followed by Meristogenys orphnocnemis (10.1%). The high species diversity and richness in THP could be due to the rich topography of this park, which provides ample feeding, breeding and shelter for frogs.